Molecular Manipulations of a Utility Nitrogen–Heterocyclic Carbene by Sodium Magnesiate Complexes and Transmetallation Chemistry with Gold Complexes. Issue 41 (19th June 2018) - Hernán‐Gómez, Alberto; Uzelac, Marina; Baillie, Sharon E.; Armstrong, David R.; Kennedy, Alan R.; Fuentes, M. Ángeles; Hevia, Eva
Abstract: Expanding the scope and applications of anionic N‐heterocyclic carbenes (NHCs), a novel series of magnesium NHC complexes is reported using a mixed sodium–magnesium approach. Sequential reactivity of classical imidazol‐ 2‐ylidene carbene IPr with NaR and MgR2 (R=CH2 SiMe3 ) affords [(THF)3 Na(μ‐IPr − ) MgR2 (THF)] (2 ) [IPr − =:C{[N(2, 6‐ i Pr2 C6 H3 )]2 CHC] containing an anionic NHC ligand, whereas surprisingly sodium magnesiate [NaMgR3 ] fails to deprotonateIPr affording instead the redistribution coordination adduct [IPr 2 Na2 MgR4 ] (1 ). Compound2 undergoes selective C2‐methylation when treated with MeOTf furnishing novel abnormal NHC complex [{ a IPr Me MgR2 }2 ] (3 ). Dissolving3 in THF led to the dissociation of this complex into MgR2 and a IPr Me with the latter isomerizing to the olefinic NHCIPr=CH2 . The ability of2 and3 to transfer their anionic and abnormal NHC ligands, respectively to Au I metal fragments has been investigated allowing the isolation and structural characterization of [RAu(μ‐IPr − )MgR(THF)2 ] (4 ) and [ a IPr Me AuR] (5 ) respectively. In both cases transfer of an alkyl R group is observed. However while3 can also transfer its abnormal NHC ligand to give5, in4 the anionic NHC still remains coordinated to Mg via its C4 position, whereas the AuR fragment occupies the C2 position previously filled by a donor‐solvated {Na(THF)3 } + cation. Abstract : Normal or abnormal, it's still gold ! Novel NHC stabilised Au I alkyl complexes have been accessed via a transmetallation approach based on a mixed Na/Mg platform containing an anionic NHC as a precursor.